PENGARUH KECEMASAN TERHADAP KADAR GLUKOSA DARAH PADA PENDERITA DIABETES MELITUS DI WILAYAH PUSKESMAS BANYUANYAR SURAKARTA - Murdiningsih, Dyah Surti; Ghofur, Gun Gun Abdul (Universitas Sahid Surakarta, 2013)
Health problems tend to increase, mental health is an issue that most real improvement. Some physical illnesses can cause anxiety in a person. A person with a chronic disease, prone to anxiety sufferers Diabetes is one of them. Â The purpose of this study is the effect of anxiety on blood glucose levels in people with diabetes mellitusÂ inÂ SurakartaÂ BanyuanyarÂ RegionalÂ Health Center.Â HypothesisÂ There is a positive effect of anxiety on blood glucose levelsÂ in people with diabetes mellitusÂ in the PHC Banyuanyar Surakarta. Â InÂ this studyÂ sample wasÂ respondents with Diabetes MellitusÂ (DM)Â type 2Â Surakarta region Banyuanyar Health Center. ByÂ samplingÂ theÂ totalÂ sampling withÂ gaugeÂ ScaleÂ anxiety scale and blood glucose levels of people with Diabetes Mellitus (DM) Type 2. Â BasedÂ on calculations using theÂ computer programÂ SPSSÂ 15.0 for WindowsÂ obtained the value of rÂ count (0.754)> rÂ Â table (0.339) or (p = 0.000 <0.05) so that HaÂ is accepted,Â it meansÂ a significant differenceÂ betweenÂ theÂ levels ofÂ anxietyÂ bloodÂ glucoseÂ in patients with diabetes mellitus in the Greater Surakarta Banyuanyar Health Center. Â Â Distribution results based on Blood Glucose Levels of respondents can be seen that the mostÂ dominantÂ isÂ the Blood GlucoseÂ LevelsÂ respondentsÂ inÂ the category DMÂ (â¥Â 200)Â that is equal to 16 or 47.1%.